A Preliminary List of Horizontally Transferred Genes in Prokaryotes Determined by Tree Reconstruction and Reconciliation - Jeong, Hyeonsoo; Nasir, Arshan (Frontiers in Genetics, 2017)
Genome-wide global detection of genes involved in horizontal gene transfer (HGT) remains an active area of research in medical microbiology and evolutionary genomics. Utilizing the explicit evolutionary method of comparing topologies of a total of 154,805 orthologous gene trees against corresponding 16S rRNA ‘reference’ trees, we previously detected a total of 660,894 candidate HGT events in 2,472 completely-sequenced prokaryotic genomes. Here, we report an HGT-index for each individual gene-reference tree pair reconciliation, representing the total number of detected HGT events on the gene tree divided by the total number of genomes (taxa) member of that tree. HGT-index is thus a simple measure indicating the sensitivity of prokaryotic genes to participate (or not participate) in HGT. Our preliminary list provides HGT-indices for a total of 69,365 genes (detected in >10 and <50% available prokaryotic genomes) that are involved in a wide range of biological processes such as metabolism, information, and bacterial response to environment. Identification of horizontally-derived genes is especially important to combat antibiotic resistance and is a step forward towards reconstructions of improved phylogenies describing the history of life. Our effort is thus expected to benefit ongoing research in the fields of clinical microbiology and evolutionary biology.